134k views
0 votes
Please help me branniest

Any answer without proof will be reported

Please help me branniest Any answer without proof will be reported-example-1

1 Answer

6 votes

Choice B is correct. The two lines cross at (2,-3)

As algebraic proof, you can plug in (x,y) = (2,-3) into each equation and verify like so

y = 2x-7

-3 = 2(2) - 7 ... replace x with 2, y with -3

-3 = 4 - 7

-3 = -3 .... true equation

Repeat for the second equation

y = -x-1

-3 = -2-1 .... replace x with 2, y with -3

-3 = -3 ... true equation

both equations are true when (x,y) = (2,-3) so the solution to the system has been confirmed.

User Phil Degenhardt
by
5.8k points